On solutions defined on an axis for differential equations with shifts of the argument - Chaikovs'kyi, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We consider linear first-order differential equations with shifts of arguments with respect to functions withvalues in a Banach space. Sufficient conditions for the existence of nontrivial solutions of homogeneousequations are obtained. Ordinary differential equations are constructed for which all solutions defined on anaxis are solutions of a given equation with shifts of the argument.